2005
DOI: 10.1073/pnas.0501962102
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of a 3′- O -allyl photocleavable fluorescent nucleotide as a reversible terminator for DNA sequencing by synthesis

Abstract: DNA sequencing by synthesis (SBS) offers an approach for potential high-throughput sequencing applications. In this method, the ability of an incoming nucleotide to act as a reversible terminator for a DNA polymerase reaction is an important requirement to unambiguously determine the identity of the incorporated nucleotide before the next nucleotide is added. A free 3 -OH group on the terminal nucleotide of the primer is necessary for the DNA polymerase to incorporate an incoming nucleotide. Therefore, if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…These include next-generation sequencing approaches (1)(2)(3), single molecule sequencing (4), labeling of DNA and PCR amplificates, e.g., for microarray analysis (5)(6)(7)(8), DNA conjugation (9), or the in vitro selection of ligands such as aptamers by SELEX (systematic enrichment of ligands by exponential amplification) (10). Furthermore, utilizing the intrinsic properties of DNA in combination with chemically introduced functionalities provides an entry to new classes of nucleic acids-based hybrid materials (9).…”
mentioning
confidence: 99%
“…These include next-generation sequencing approaches (1)(2)(3), single molecule sequencing (4), labeling of DNA and PCR amplificates, e.g., for microarray analysis (5)(6)(7)(8), DNA conjugation (9), or the in vitro selection of ligands such as aptamers by SELEX (systematic enrichment of ligands by exponential amplification) (10). Furthermore, utilizing the intrinsic properties of DNA in combination with chemically introduced functionalities provides an entry to new classes of nucleic acids-based hybrid materials (9).…”
mentioning
confidence: 99%
“…For example, Metzker et al (1994) first described the synthesis and incorporation of a 3Ј-O-allyl-dATP by DNA polymerase, with the O-allyl group being removed using the well-known palladium (Pd) catalyst chemistry (Hayakawa et al 1986(Hayakawa et al , 1993Honda et al 1997). Recently, Ruparel et al (2005) reported the synthesis of the first fluorescently labeled 3Ј-O-allyldNTPs. These unique reversible terminators require dual deprotection steps using UV light to cleave the fluorophore from the nucleotide (Fig.…”
Section: Crtmentioning
confidence: 99%
“…This product was then deallylated using a Pd-catalyzed deallylation mixture [1ϫ Thermopol I reaction buffer/Na 2 PdCl 4 /P(PhSO 3 Na) 3 ]. The active Pd catalyst is generated from Na 2 PdCl 4 and a ligand P(PhSO 3 Na) 3 (TPPTS) to mediate the deallylation reaction in DNA compatible aqueous condition to simultaneously cleave both the fluorophore and the 3Ј-O-allyl group (28). The deallylated product (2) was also analyzed by using MALDI-TOF MS (Fig.…”
Section: Design and Synthesis Of Chemically Cleavable Fluorescent Nucmentioning
confidence: 99%
“…We have previously established the feasibility of performing SBS on a chip using four photocleavable fluorescent nucleotide analogues (26) and discovered that an allyl group can be used as a cleavable linker to bridge a fluorophore to a nucleotide (27). We have also reported the design and synthesis of two photocleavable fluorescent nucleotides as reversible terminators for polymerase reaction (28,29).…”
mentioning
confidence: 99%